1990
DOI: 10.1515/znc-1990-0510
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Herbicide Binding Site in Isolated Photosystem II Core Complexes from a Flat-Bed Isoelectrofocusing Method

Abstract: Isoelectrofocusing has been used to separate various chlorophyll-protein complexes of photosystem two (PS II). Light-harvesting complexes containing chlorophyll a and chlorophyll b (LHC II) were located in bands having p/s in the region of 4.5. At slightly higher pH other light-harvesting complexes containing little or no chlorophyll b were found. In the most basic region of the isoelectrofocusing gel, were located PS II core complexes characterized by con­taining the proteins of CP47, CP43, D 1, D 2 and α-sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1992
1992
1995
1995

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Some effects that have been attributed to the phosphorylation of the PSII core polypeptides include an inhibition of light-saturated PSII electron transfer (18,19), a destabilization of the anionic semiquinone QB-, and an accumulation of QA- (17). Recently, the existence of PSII core populations that differ in the extent of phosphorylation of their polypeptides has been described (9,11). It was possible to convert the cores from one form to another in the dark; however, this conversion was never complete because at least two differently phosphorylated populations were always detected (see Table II Table IV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some effects that have been attributed to the phosphorylation of the PSII core polypeptides include an inhibition of light-saturated PSII electron transfer (18,19), a destabilization of the anionic semiquinone QB-, and an accumulation of QA- (17). Recently, the existence of PSII core populations that differ in the extent of phosphorylation of their polypeptides has been described (9,11). It was possible to convert the cores from one form to another in the dark; however, this conversion was never complete because at least two differently phosphorylated populations were always detected (see Table II Table IV.…”
Section: Discussionmentioning
confidence: 99%
“…Control thylakoids were illuminated in the absence of ATP and MgCl2, washed with the suspension buffer, dark-adapted for 2 h, and finally NaF was added to a concentration of 5 mm. PSII membranes were isolated (3), solubilized in 1% DM (0.5 mg of Chl mnL1), and then applied to the cathode region of a flat-bed of granulated gel (9). The bed (2.5 x 22 cm) of Ultrodex (LKB) was prepared in 0.1 M glycine, 0.…”
Section: Materials and Methods Phosphorylation And Isolation Of Membrmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently shown that a heterogeneity, which is probably regulated by light conditions, exists in the phosphorylated PSII core populations in grana membranes (Giardi et al 1990. These PSII cores show different QB pocket functioning with respect to plastoquinone (PQ) binding (Giardi et al 1992a).…”
Section: Introductionmentioning
confidence: 99%